A Monthly Dynamic Consumer Expenditure System for Germany with Different Kinds of Households - Veall, Michael R.; Zimmermann, Klaus F. (The Review of Economics and Statistics, 1986)
Michael R. Veall, Klaus F. Zimmermann, A Monthly Dynamic Consumer Expenditure System for Germany with Different Kinds of Households, The Review of Economics and Statistics, Vol. 68, No. 2 (May, 1986), pp. 256-264